Inhibition of starch retrogradation by soluble soybean polysaccharides with different molecular weights and degrees of esterification - Zhao, Qizhu (My University, 2021)
Nowadays, cooked rice and noodles are the staple foods of many people, while they are difficult to be stored due to the high moisture content. Recently, a new polysaccharide-soluble soybean polysaccharide (SSPS), has been found can inhibit starch retrogradation. However, there has been some inconsistent results in previous studies. However, there are many inconsistent results of its anti-retrogradation ability, and its mechanism and the influencing factors are still not clear. Therefore, this study investigates the effects of structural elements: molecular weight (Mw) and degree of esterification (DE) of SSPS on starch gelatinization and retrogradation characteristics at 90% moisture content, and discuss the mechanism. The rapid visco-analysis result showed that at the same DE, the SSPS with lower Mw had the better effect on reducing pasting viscosity, while when the Mw is too low (40×104 Da), the viscosity was no longer affected. At the same Mw, the SSPS with lower DE exerted better effect on viscosity decrease. The results of water holding capacity of gels and low-field nuclear magnetic resonance further indicate that the structure of SSPS influences its hydrophilic ability. SSPS with high Mw had weak water binding ability, while the SSPS with medium Mw could maintain enough hydrophilic groups on the main chain, and the SSPS with lower DE had better water binding ability. The texture profile analysis results indicate that the softer the gel texture after 14-day storage, the lower the relative crystallinity. In summary, SSPS with medium Mw and low DE had the best anti-retrogradation effect, while that with high Mw and high DE performed the worst. The results confirmed that the mechanism of the anti-retrogradation effect of SSPS was to influence gelatinization, which mainly depends on the control of water and interaction with starch molecules.